The Influence of Customer Satisfaction on Visiting Decisions Through Customer Loyalty at the Betawi Babeh Sadeli Restaurant, Pondok Aren, South Tangerang, Banten Province - Marie, Andhalia Liza; Prasetio, Arton Briyan (Institut Pariwisata Trisakti, 2025)
This study aims to analyze the influence of customer satisfaction on visiting decisions, mediated by customer loyalty, among consumers of Babeh Sadeli Betawi Restaurant in Pondok Aren, South Tangerang. The approach employed was quantitative, utilizing an explanatory survey method with 150 respondents selected through a purposive sampling technique. Data were collected through a closed-ended questionnaire with a five-point Likert scale and analyzed using path analysis, with the help of bootstrapping, to test the mediation effect. The results showed that customer satisfaction has a positive and significant impact on loyalty and visiting decisions, both directly and indirectly. Customer loyalty proved to be a substantial mediator that strengthens the relationship between satisfaction and visiting choices. This finding confirms that positive experiences with food, taste, service, atmosphere, and price can shape satisfaction, leading to loyalty and repeat visits. Customer satisfaction and loyalty play an essential role in retaining customers of local ethnic restaurants. The practical implications of this study suggest that restaurant managers should maintain the quality of the customer experience holistically, prioritize the authenticity of Betawi culture, and refine digital promotion strategies to enhance consumer loyalty and informed decision-making. Keywords: customer satisfaction, customer loyalty, visiting decisions